Education Abroad as Knowledge Diplomacy: A Consortium Approach to Increasing Students’ Participation in Study in China - Huang, Cen; Liu, Wei (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2023)
Education abroad experiences are beneficial to students’ personal growth, intercultural awareness, and career preparedness. However, the rate of Canadian postsecondary students’ participation in education abroad has been low, particularly in Asia. Lack of financial resources and uncertainty in credit transfer are identified as common challenges that stop students from pursuing such opportunities. In this paper, the Canada Learning Initiative in China (CLIC), a consortium of 12 top Canadian research-intensive universities, is introduced as a model to increase students’ participation in study abroad in China. After an introduction to the design of the program, a thematic analysis is conducted on students’ self-reported learning experiences to glean the impact of such an initiative. This study shows that consortia can be utilized as an effective approach to promoting the rate of students’ participation in education abroad. Based on students’ learning outcomes, the paper argues that an education abroad consortium is an ideal way to achieve knowledge diplomacy.